All‐Inorganic CsPb1−xGexI2Br Perovskite with Enhanced Phase Stability and Photovoltaic Performance. Issue 39 (29th August 2018) - Yang, Fu; Hirotani, Daisuke; Kapil, Gaurav; Kamarudin, Muhammad Akmal; Ng, Chi Huey; Zhang, Yaohong; Shen, Qing; Hayase, Shuzi
Abstract: Compared with organic‐inorganic perovskites, all‐inorganic cesium‐based perovskites without volatile organic compounds have gained extensive interests because of the high thermal stability. However, they have a problem on phase transition from cubic phase (active for photo‐electric conversion) to orthorhombic phase (inactive for photo‐electric conversion) at room temperature, which has hindered further progress. Herein, novel inorganic CsPb1− x Ge x I2 Br perovskites were prepared in humid ambient atmosphere without a glovebox. The phase stability of the all‐inorganic perovskite was effectively enhanced after germanium addition. In addition, the highest power conversion efficiency of 10.8 % with high open‐circuit voltage ( V OC ) of 1.27 V in a planar solar cell based on CsPb0.8 Ge0.2 I2 Br perovskite was achieved. Furthermore, the highest V OC up to 1.34 V was obtained by CsPb0.7 Ge0.3 I2 Br perovskite, which is a remarkable record in the field of all‐inorganic perovskite solar cells. More importantly, all the photovoltaic parameters of CsPb0.8 Ge0.2 I2 Br perovskite solar cells showed nearly no decay after 7 h measurement in 50–60 % relative humidity without encapsulation. Abstract : Germanium is for the first time reported to incorporate in all‐inorganic CsPbI2 Br perovskite and lead to enhanced phase stability and photovoltaic performance. A large V OC of up to 1.34 V and a high PCE of 10.8 % were achieved by planar perovskite solar cells (PSCs) that were prepared in an uncontrolled humid air atmosphere without a glovebox, which are remarkable records for the CsPbI2 Br PSCs.